Decent work and healthy employment: a qualitative case study about Colombian millennials (2020)
The purpose of this paper is to show how a group of Colombian millennials perceive different aspects of working life and how their ideas about job satisfaction, professional expectations, and levels of autonomy are related to contemporary demands about inclusion, diversity, equity, autonomy, and control. With this objective, 167 semi-structured interviews were conducted with millennials who work at 10 Colombian companies from the manufacturing and service sectors, located in the 5 main cities of the country. With a qualitative approach in the interviews, the research team used a strategy inspired by the technique of generating visual structures associated with grounded theory. It is concluded that new generations of Colombian workers know of the importance of rewards and autonomy in work and are more critical and less passive in the face of unhealthy working conditions. At the same time, their conduct and speeches are the consequence of the characteristics of the Colombian labour market. The document responds to the need to deepen the debates on welfare and happiness in organizations and to include the demands of millennials in the reflective and political horizon of the ideas of healthy employment and decent work. In practice, this article seeks to demystify ideas about millennials in Colombia and critically contribute to reflection on intergenerational relations in organizations and salary and welfare models. As a Latin American case, it is an original contribution that avoids the common places and the frivolity with which the insertion of the new generations into the working world has been analysed.